The Attitude–Behaviour Gap: A Systematic Review of the Green Purchase Paradox and Consumer Sensemaking - Aung, Ye Yint Khan (Auckland University of Technology, 2025)
This systematic literature review (SLR) investigates the paradoxical tensions consumers face in green purchasing decisions, contributing to the attitude–behaviour gap, and how consumers make sense of these tensions to develop strategies that overcome this gap. Despite favourable environmentally friendly attitudes, empirical evidence shows consumers frequently opt for less sustainable options. Hence, the attitude–behaviour gap poses significant practical challenges to more sustainable consumption habits, gaining prominent interest among scholars. However, the fragmented literature with inconsistent findings highlights the need for a comprehensive synthesis and integration of the theories, paradigms and findings. By employing paradox theory, this SLR not only delineates the conflicting yet coexisting forces causing tensions behind consumer choices in green purchasing but also enriches the comprehension of how consumers make sense of these contradictory values. This review aims to provide valuable insights to academics, practitioners and policymakers in approaching the attitude–behaviour gap through the paradoxical lens, i.e., recognising and addressing these conflicting tensions consumers experience when they make green purchases, thereby fostering more sustainable consumption habits.